How to buy real estate overseas - Peddicord, Kathleen (John Wiley & Son, 2013)
How to buy real estate overseas explains one of the best options available today for diversification, as set protection, and a safe haven for wealth. This book offers detailed advice including: - Strategies for choosing the right property in the right country, including buying oppotunities in "crisis markets", income generation, and groth potental. - Twenty great countries to consider for quenching you wanderlust. - The unexpected realities of buying overseas - such as rights of possession, " margarita madness", your gringo status - and how to overcome them.